Chile y Brasil : intereses conjuntos en el Pacífico - Porto de Oliveira, Amaury (Estudios Internacionales, 1991)
Taking as a hypothesis the theory of long cycles of Kondratiev, in the present work it is argued that the model of the Third Industrial Revolution will result only from common efforts. The inevitability of commercial megablocks is thus rejected. Hence the importance of the Asia-Pacific region, since this multilateralist world economy model is being discussed there as the beneficial alternative to dividing the world into dire megablocks. However, Latin American countries are not included in this future development pole. It becomes evident, then, the need to take advantage of the joint interests between Chile and Brazil to try to reverse this situation and organize themselves into regional political-economic formations. In the implementation of a non-competitive multilateralist world economy model, both nations have an excellent opportunity to insert themselves internationally.